VALIDATED AND QUANTIFIED STABILITY INDICATING STRESS DEGRADATION STUDY OF ORAL ANTI-DIABETIC AGENT CANAGLIFLOZIN BY RP-HPLC METHOD - MURUGESAN, ARULSELVAN; MATHRUSRI ANNAPURNA, MUKTHINUTHALAPATI (International Journal of Applied Pharmaceutics, 2021)
Objective: The present investigation is aimed to develop and validate, a simple, consistent and sensitive stability-indicating reverse phase-high performance liquid chromatography (RP-HPLC) method for the determination of oral anti-diabetic drug Canagliflozin in bulk and pharmaceutical dosage form as per the International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use (ICH-Q2 (R1)). Methods: The chromatographic separation was achieved by using Reverse Phase-High Performance Liquid Chromatography (RP-HPLC) ZORBAX C18 (250 mm x 4.6 mm, 5μm particle size) with a mobile phase consisting of Acetonitrile: Water in a ratio of 53:47% v/v at a flow rate of 1 ml/min with an injection volume of 20 μl. Results: The Retention time of the drug Canagliflozin was found to be 2.36±0.05 min and detected at 214 nm UV wavelength. The linear regression equation was found to be y = 60702x–2156.2 with a correlation coefficient 0.9999. Stress degradation studies were performed by exposing the Canagliflozin into acidic, alkaline, oxidative, thermal and photolytic stress conditions with active samples withdrawn at different time intervals as per ICH guidelines. Conclusion: The proposed Reverse Phase High-Performance Liquid Chromatography (RP-HPLC) method was found to be robust, precise and specific for estimation of Canagliflozin in pharmaceutical dosage forms.